Políticas públicas e desenvolvimento Territorial: o Programa Territórios da Cidadania no Estado de São Paulo - Souza, Sérgio Pereira de [UNESP] (2015)
The purpose of this PhD thesis is to address the process of institutionalization of the Citizenship Territories (CTs) and analyze the socioeconomic and spatial repercussions of PROINF in the territorial development of the state of São Paulo. We defend the thesis that the institutionalization of these territories has caused an unequal and exclusionary development of the CTs in this state of the federation. We have used the following methodological procedure to achieve this purpose: literature survey, collection and systematization of quantitative data and qualitative information, conduct of interviews with 80 stakeholders in the territory (managers, representatives, and recipients) involved in the implementation process of PROINF in the CT of the state of São Paulo, specifically in the municipalities of Teodoro Sampaio (Pontal do Paranapanema), Registro (Ribeira Valley) and Itapeva (Southwest São Paulo) and documentary analysis of PROINF and PTC. To understand the operationalization and methodological and conceptual constitution involving this process, it is necessary to make use of the instruments employed by the Federal Government to strengthen the territorial development through the implementation of a mix of actions aimed at the promotion of rural areas with the implementation of infrastructure and equipment that facilitate the production and sale of agricultural products from family farms in the territories. The strategies used by local actors were the parameters used to understand the process of operationalization of PROINF as one of the axes of PTC...